Full stack AngularJS for Java developers : build a full-featured web application from scratch using AngularJS with Spring RESTful - Soni, Ravi Kant (Apress, 2017)
Get introduced to full stack enterprise development. Whether you are new to AngularJS and Spring RESTful web services, or you are a seasoned expert, you will be able to build a full-featured web application from scratch using AngularJS and Spring RESTful web services.Ƶll stack web development is in demand because you can explore the best of different tools and frameworks and yet make your apps solid and reliable in design, scalability, robustness, and security. This book assists you in creating your own full stack development environment that includes the powerful and revamped AngularJS, and Spring REST. The architecture of modern applications is covered to prevent the development of isolated desktop and mobile applications.¹ the time you reach the end of this book you will have built a full-featured dynamic app. You will start your journey by setting up a Spring Boot development environment and creating your RESTful services to perform CRUD operations. Then you will migrate the front-end tools?AngularJS and Bootstrap?into your Spring Boot application to consume RESTful services. You will secure your REST API using Spring Security and consume your secured REST API using AngularJS. What You'll Learn: Build a REST application with Spring Boot Expose CRUD operations using RESTful endpoints Create a single page application by integrating Angular JS and Bootstrap in Spring Boot Secure REST APIs using Spring Security Consume secured RESTful Services using Angular JS Build a REST client using a REST template to consume RESTful services Test RESTful services using the Spring MVC Test Framework.